Innovative Technologies for Literature Education Based on International Assessment Criteria - Achilova Emina Sadulloevna (Periodica Journal, 2025)
"The articles discuss modern educational technologies and methods of their application in the teaching process. The issue of the effectiveness of innovative technologies is analyzed. The ways of using interactive methods are demonstrated."
Keywords: Modern educational technologies; PISA; CLIL; CBL